Merilska blaznost ali o sprevrženi rabi nekega znanstvenega orodja - Kramberger, Taja (Šolsko polje, 2010)
In this article we discuss the processus of destruction which captured - through neoliberal hegemony - institutions of the intellectual autonomy. Th e purpose of this destruction is such a social homogenisation that it is in factthe actual opposite of the republican or democratic type of egalitarism: two basic social categories are about to be formed; the smaller one, composed by the holders of property and social power, and the bigger one, to which all the others belong to. Both are getting, each by itself, ideologically and economically homogenious. Education is changing itself into the function of this new social segregation; to carry out this segregation the destruction of almost all social autonomies, especially of the intellectual one, is required.Th ey are gradually replaced by the market or mercantile homogenity, introducing the unique criterion for all social life: the profi t of the first category.
Keywords: antiintelectualism; antiintelektualizem; classifications; lestvice; merjenja; mesurements; neoliberalism; neoliberalizem; raziskovanje; research; science; university; univerza; vzgoja in izobraževanje; znanost